واقع الادارة البيئية في المؤسسة الصناعية الجزائرية دراسة حالة مؤسسة الدهن سوق اهراس - نور الهدى بوناب; صفاء زمزوم (My University, 2019)
The objective of the research is to examine the level of adoption of the environmental management system by the National Painting Company (ENAP), it consists in particular in establishing a diagnosis of the availability of internal resources and the potentialities of environment management. The results revealed three important aspects: the first is the weak environmental orientation of ENAP, the second is the availability of certain resources and medium opportunities for environmental management, and the third is the existence of numerous obstacles and constraints that hinder the company's environmental commitment. The study concluded by presenting some suggestions that could help the company managers improve the environmental management of their activities and improve their performance in the areas concerned. ...........................................